Implications of extremes of body weight on pregnancy outcome. (7th June 2011) - Anand, S; Rana, S; Maiti, S
Abstract : Objective: To compare the pregnancy outcomes of women with morbid obesity (body mass index (BMI) ≥40) and extremely underweight (BMI<16) with that of women with normal BMI (18.5 to 24.99) Design: retrospective observational study over 3 years. Setting: Penine Acute Hospitals NHS trust. Results: The total number of deliveries during this period was 33 509.The number of women pregnant with normal BMI were 15 275(46%). There were 580 women (2%) with morbid obesity and 40 women (0.1%) were extremely underweight during the same period. Only 11% of obese women took folic acid prepregnancy. Only 1% of women in the normal BMI category had gestational diabetes whereas 9% of morbidly obese women had gestational diabetes. The rates of induction (28%) and caesarean section (42%) were higher in the high BMI group. 4% of the babies were macrosomic (birth weight≥4.5 kg) in the high BMI group and 1% in the normal BMI group. The incidence of shoulder dystocia was 2% in high BMI category and 1% in the normal BMI group. 25% of babies in the low BMI group had a birth weight of less than 2.5 kg. This was 8% in the normal and 4% in the high BMI categories. Conclusions: The importance of pre pregnancy counselling and weight reduction cannot be over emphasised. Efforts should be directed in extremely underweight women to attain adequate pre pregnancy weight. Further research is needed to determine the optimal weight gain/reduction during pregnancy for women in different BMI categories.